Scrutinizing the influence of strain‐induced fiber orientation on the melt rheological behavior of short aramid fiber/thermoplastic elastomer composite using rubber process analyzer. Issue 6 (18th October 2012) - Shibulal, G. S.; Naskar, K.
Abstract The effect of fiber loading and its orientational changes on the melt rheological behavior of a short aramid fiber reinforced ethylene‐octene copolymer was explored as function of dynamic strain and frequency using a Rubber Process Analyser (RPA). The rheological responses such as the storage modulus and complex viscosity to a cyclic dynamic strain sweep and subsequent linear viscoelastic (LVE) frequency sweep were performed to probe the orientational changes of the short fiber within the sample. An enhanced elastic shear modulus was observed at the low strain regime with a few numbers of repeated strain sweeps and level off thereafter. This can be attributed to the orientational changes of the short fiber from an initial random orientation to a well‐ordered concentric fiber string and the string–string packing with repeated oscillatory shear strain. The complex viscosity measured as a function of LVE frequency sweep having the influence of a pre strain history was also found to increases in first few cycles, but very interestingly the complex viscosity measured at all the frequency sweep cycles shows similar values, which are not subjected to any strain history. The optical microscopic images of the samples before and after the RPA analyses clearly support the possibility of fiber orientations and their subsequent packing with repeated strain sweeps. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013